The Use of Aegisub Subtitling Editor In Subtitling Class in IAIN Surakarta - Arina Rohmatika; Pipin Devi Arista (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
Subtitling editor softwares have been widely used as teaching media in education field such as in teaching English. To be more specific, in Subtitling class in IAIN Surakarta, several well-known subtitling editor softwares have been so far implemented by the lecturers as teaching media whereby students can do their tasks in subtitling class. Aegisub is one of those softwares which is used in English Education Department of IAIN Surakarta. This study aims to know the implementation of Aegisub in subtitling class of the fourth semester students of English Education Department, IAIN Surakarta and to learn about the benefits and challenges during the implementation of this subtitling editor use in subtitling class. This study implements descriptive qualitative method. Data was gathered through interviews and questionnaire while data triangulation was used to analyze it. Overall, the results shows that Aegisub is easy to be implemented by the students or user-friedly, having a good operating system compatibility, having a series of Easy-to-Follow Instruction, rich in feature and it also can increase students’ motivation both in doing the subtitling tasks and having the class. Moreover, some challenges were also found in its implementation such as recognizing all the tools or memorizing it during the editing process; difficulty in changing from one tool to another, matching the text of subtitle and the time of video process, and such technical problem like it could not be installed in every operating system and lastly difficulty in inputting the subtitle.